Perancangan Strategi Bisnis Cafe Pada UKM XYZ Menggunakan Analisis PESTLE, SWOT, dan IFE EFE - Naila Khairunnisa; Shofi Kirana Aryati; Nazwa Priditya; Alysha Dzahabiyya Aurora Riyadi; Diah Pitaloka Saraswati; Lindawati Kartika (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the current era of rapidly developing globalization, rapid technological changes, shifting consumer preferences, and global market dynamics encourage Small and Medium Enterprises (SMEs) to adapt, innovate, and strategize intelligently. This article discusses a business strategy designed for SME XYZ, a company operating in the food and beverage sector, especially in the coffee shop industry which is growing rapidly in Indonesia. This research uses the PESTLE and SWOT approaches to analyze the internal and external conditions of UKM XYZ. The analysis results show that SME XYZ has internal strengths such as high-quality coffee, excellent service, and a competent management team, as well as external opportunities such as Gen Z lifestyle trends and online ordering. However, challenges such as high operational costs and inflation need to be addressed. Recommended strategies include strengthening branding, increasing operational efficiency, and presenting innovative menus. With the right strategy, SME XYZ has the potential to become a major player in the food and beverage industry.